BANDED MICROSTRUCTURE IN FORGED 18CrNiMo7-6 STEEL (Metallurgy and Foundry Engineering, 2013)
18CrNiMo7-6 steel, after hot forging, exhibits a distinct banding of ferritic-pearlitic microstructure, probably related to the segregation of alloying elements during the ingot crystallization. The heat treatment allowing to obtain bainitic microstructure in this steel is described in the paper. The obtained bainitic microstructure exhibits only very small traces of banding.